The influence of the menstrual cycle on muscle strength and power performance - Romero-Moraleda , B.; Del Coso, J.; Gutiérrez-Hellin, J.; Ruiz-Moreno, C.; Grgic, J.; Lara, B. (Journal of Human Kinetics, 2019)
This study aimed to investigate the fluctuations of muscle performance in the Smith machine half-squat exercise during three different phases of the menstrual cycle. Thirteen resistance-trained and eumenorrheic women volunteered to participate in the study (58.6 ± 7.8 kg, 31.1 ± 5.5 years). In a pre-experimental test, the half-squat one-repetition maximum (1RM) was measured. Body mass, tympanic temperature and urine concentration of the luteinizing hormone were estimated daily for ~30 days to determine the early follicular phase (EFP), the late follicular phase (LFP), and the mid-luteal phase (MLP) of the menstrual cycle. On the second day of each phase, performance of the Smith machine half-squats was assessed using 20, 40, 60 and 80% of one repetition maximum (1RM). In each load, force, velocity, and power output were measured during the concentric phase of the exercise by means of a rotatory encoder. The data were analyzed using one-way repeated measures ANOVA coupled with magnitude-based inferences. Overall, force, velocity and power output were very similar in all menstrual cycle phases with unclear differences in most of the pairwise comparisons and effect sizes >0.2. The results of this investigation suggest that eumenorrheic females have similar muscle strength and power performance in the Smith machine half-squat exercise during the EFP, LFP, and MLP phases of the menstrual cycle.